1991
DOI: 10.1007/bf01320228
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in biochemical composition of body walls, gonads and pyloric caeca in two populations ofSclerasterias mollis (Echinodermata: Asteroidea) during the annual reproductive cycle

Abstract: Abstract. Seasonal changes in biochemical composition of tissues are compared in a shallow inshore and deeper offshore population of the seastar Sclerasterias mollis (Hutton, 1872) on the Otago shelf, New Zealand, from 1985 to 1986. The biochemical composition of the body wall, gonads and pyloric caeca of the two populations did not differ greatly, even though reproductive output and nutrient storage of reserves were consistently higher in the offshore population. The biochemical composition of the ovaries and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…The stomach and the body wall showed no significant variations in lipid content between sexes and during the reproductive cycle. Barker & Xu (1991) also report little variation in the lipid content of the body wall over the annual reproductive cycle for 2 populations of Sclerasterias mollis. In contrast, lipid content of the gonads and pyloric caeca varied considerably.…”
Section: Biochemical and Energetic Componentsmentioning
confidence: 85%
“…The stomach and the body wall showed no significant variations in lipid content between sexes and during the reproductive cycle. Barker & Xu (1991) also report little variation in the lipid content of the body wall over the annual reproductive cycle for 2 populations of Sclerasterias mollis. In contrast, lipid content of the gonads and pyloric caeca varied considerably.…”
Section: Biochemical and Energetic Componentsmentioning
confidence: 85%
“…It is also not excluded partially due to difference in geographic distribution. For instance, we have found that geographic difference affected biochemical composition of the different populations of starfish [35,36]. When comparing the scavenging radical effect of PEP with polysaccharides from other marine species, the scavenging ability of PEP on superoxide anion (43.30%) at the concentration of 1mg‱mL −1 is stronger than other species, for example, the ability is only 26.17% for Sipunculus Nudus [37].…”
Section: Discussionmentioning
confidence: 99%
“…Asterinid species have different reproductive patterns, including seasonal or continuous breeding periodicity (Carvalho and Ventura, 2002;Barker and Xu, 1991b;Byrne, 1992;Paik et al, 2005;Pastor-de-Ward et al, 2007;Mariante et al, 2010;Micael et al, 2011;BenĂ­tez-villalobos and MartĂ­nez-garcĂ­a, 2012). The differences are related to many environmental factors, including temperature, hydrodynamics, the quantity and quality of available food, and photoperiod.…”
Section: Introductionmentioning
confidence: 99%